2011
DOI: 10.1007/s11105-011-0303-8
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Human Tissue-Plasminogen Activator in Hairy Roots of Oriental Melon (Cucumis melo)

Abstract: The human tissue plasminogen activator (t-PA) is a thrombolytic protein that plays a key role in fibrinolysis by converting the plasminogen into plasmin which degrades fibrin clots in blood vessels. The t-PA gene encoding the human tissue plasminogen activator was cloned and expressed under transcriptional control of single and multiple rooting loci promoter (rolD) promoters in hairy roots derived from Oriental melon. t-PA gene integration in the genome of hairy roots was confirmed by PCR. Increased transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…Recently, it was demonstrated that the AtMC4 autoproteolytic process is Ca +2 -dependent (Watanabe and Lam 2011). It should be noted that under many stress conditions, e.g., salinity, cold and heat stress, the concentration of cytosolic calcium increases dramatically (Xiong et al 2002; Kang et al 2011). It is also known that high concentrations of calcium ions is toxic for plant organelles; thus, there are some specific channels/pumps that regulate the movement of Ca +2 in and out of cells and organelles (Xiong et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was demonstrated that the AtMC4 autoproteolytic process is Ca +2 -dependent (Watanabe and Lam 2011). It should be noted that under many stress conditions, e.g., salinity, cold and heat stress, the concentration of cytosolic calcium increases dramatically (Xiong et al 2002; Kang et al 2011). It is also known that high concentrations of calcium ions is toxic for plant organelles; thus, there are some specific channels/pumps that regulate the movement of Ca +2 in and out of cells and organelles (Xiong et al 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Other factors might also be responsible for lower reteplase production in the obtained cell cultures, such as less differentiated cells and plastids (Michoux et al, 2013), instability of the recombinant protein secreted to the medium due to protease release from disrupted cells (Hong et al, 2002), or aggregation occurring when the daughter cells do not separate in the cell division (Santos et al, 2016). Nevertheless, the rtPA yield was significantly higher than the tPA production (up to 0.017%) in a hairy root system (Kang et al, 2011).…”
Section: Determination Of the Protein Content And Activity Assaymentioning
confidence: 99%
“…Shake flasks [121] Human tissue plasminogen activator (t-PA) Thrombolytic protein that converts plasminogen into plasmin Oriental Melon (Cucumis melo) Shake flasks [122] [123]…”
Section: Petunia Parodiimentioning
confidence: 99%